The Impact of Tourism on Quality of Life Based on the Perspective of Local Community in Canggu Village, Badung Regency - Fatimah Adelaida Ivan; Ni Made Sofia Wijaya; I Gusti Ngurah Widyatmaja (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The locals' quality of life has been substantially influenced by the growth of tourists in Bali's Badung Regency's Canggu Village. The locals of Canggu Village provide their opinion on how tourism affects their quality of life, which is examined in this study. Income, housing, social stability, health, education, employment prospects, job security, and happiness are the nine factors that are used to assess the quality of life. The data analysis in this study is done quantitatively utilizing Smart-PLS.The study's conclusions, which have an original sample value of 0.422, T Statistic 5.867, and p-value 0.000, show that the impact of tourism on the economic side strongly influences the community's quality of life. The socio-cultural aspect also demonstrates significant influence, with an original sample value of 0.426, T Statistic 5.789, and p-value 0.000. Similarly, the environmental aspect significantly affects quality of life, with an original sample value of 0.255, T Statistic 3.907, and p-value 0.000.From the perspective of the local community, these three aspects show that the growth in tourism activities has a significant positive impact on the quality of life of the people in Canggu Village. To enhance quality of life and optimize the benefits of tourism, it is recommended to provide training programs for local residents, promote sustainable tourism practices, educate about social risks, and strengthen environmental regulations along with community participation in environmental conservation efforts.